Differences in Halal Food Knowledge among Business Actors by Providing Digital Flipbook and E-booklet Media Education - Khikmah Widianti; Endah Budi Permana Putri (UNIVERSITAS NAHDLATUL ULAMA SURABAYA, 2023)
The current halal lifestyle is not only limited to Muslims, but many non-Muslim countries have also started implementing halal food products. This research aims to determine the effect of providing education using visual media on halal food knowledge for Surabaya culinary center businesses. This type of research is True Experimental using a pre-post test design. The sample in the research consisted of 40 respondents. The samples taken in this study used total sampling, then divided into 2 groups (digital Flipbook education group and Ebooklet group). The test analysis used was Mann Whitney okewith a significance level (α=0.05). The research results showed that there were differences in the knowledge of respondents in the groups given digital Flipbook and E-booklet media education with a p-value of P-0.003. It is hoped that further research can use the educational media E-booklets and digital flipbooks to increase knowledge of halal food.